The Role of Corporate Governance Mechanism in Optimizing Firm Performance: A Conceptual Model for Corporate Sector of Pakistan - Akbar, Ahsan (Journal of Asian Business Strategy, 2015)
Corporate governance refers to the processes that govern and direct firm managers to take decisions that are in line with the shareholders goal of wealth maximization. Various studies have been conducted in developing countries including Pakistan to investigate the relationship between corporate governance and firm performance mostly by using the conventional measures of corporate governance. The result of these studies suggests that corporate governance positively and significantly contributes towards firm performance. The aim of this study is to incorporate some important policy measures related to major players of corporate governance that are of significant importance in establishing an effective corporate governance structure in addition to the conventional measures of corporate governance. Inclusion of these variables will help the firms to create an effective corporate governance system that will lead to an increased firm performance.